Pengaruh Likuiditas, Struktur Aktiva dan Risiko Bisnis Terhadap Struktur Modal (Studi Empiris pada Perusahaan Property dan Real Estate di Bursa Efek Indonesia) - Nurul Qosidah; Fitri Romadhon (Jurnal Akuntansi, 2021)
The purpose of this study is to examine the role of the liquidity ratio, asset structure andbusiness risk in influencing the determination of capital structure. Property and real estate companies on the Indonesia Stock Exchange in 2016-2018 were employed as the research population, and obtained 39 companies as research samples. This study uses multiple linear regression analysis for hypothesis testing. The results of this study validate prior studies that test liquidity, asset structure and business risk, where liquidity and asset structure have an influence on the determination of capital structure. These results, especially in the asset structure proved consistent, although in this study the asset structure was considered from the point of view of the company's ability to manage current assets and fixed assets as determinants of capital structure. However, this study failed to prove that business risk can affect the capital structure. Keywords: Liquidity, Asset Structure, Business Risk,and Capital Structure